If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -30 = -25 Reorder the terms: -30 + p = -25 Solving -30 + p = -25 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + p = -25 + 30 Combine like terms: -30 + 30 = 0 0 + p = -25 + 30 p = -25 + 30 Combine like terms: -25 + 30 = 5 p = 5 Simplifying p = 5
| 6x+14=122-6x | | 4(3x-9)=2(6x+1) | | 3+9x=35+x | | 8+6t-3=9t+8-2t | | 3x-1=10x-85 | | 8t+6t-3=9t+8-2t | | 6x+24=16x-86 | | 5x+46=9x+14 | | x-ab=3 | | 9-z=7+z | | -3x+5=41 | | 2r+2=4r+8 | | 4(x+9)=28 | | 5k-3=12 | | x^2+2ix+2=0 | | 12=6X-4 | | 4n-11=3n-5 | | 3(5+x)=17+x | | x+x+x+(x+4)=124 | | x+x+x+x+4=124 | | 9z+7z=32 | | 9a-15=7a+11 | | 12(4x-9)=4(12x+1) | | -7x+3=4+x | | 2x+8=36 | | (x+3)=16 | | 6l-2=10 | | x^3-4x+1=0 | | 2a+5=43 | | 2x^3-4x^2+13x-5=0 | | 6(x-3)-4(x+2)=9x-(5x+3) | | 6p-3=21 |